Pengaruh E-Promotion, Kelompok Referensi, dan Kemudahan Terhadap Keputusan Pembelian Pada Marketplace Shopee - Andhifa Eka Putri; Moh Agung Surianto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The purpose of this research is to find out how e-promotion, reference groups, and ease of use influence purchasing decisions on the shopee marketplace. This research is conducted using methods of quantitative research can be understood as methods used to research on a particular population or sample, data collection using research instruments, data analysis of a statistical nature, with the aim of testing the hypothesis that has been established. The sample in this study is 160 people who have used marketplace shopee. Sampling technique is purposive sampling. The research results show that there is an influence between e-promotion, reference groups have an influence on purchasing decisions, while ease has no influence on purchasing decisions in the shopee marketplace.